Titanium-aluminum composite material and preparation method and application thereof

Through ball mill mixing and thermal isostatic molding, the problems of low density and difficult molding of titanium-aluminum composites are solved, and the preparation of titanium-aluminum composites with high density and uniformity is achieved, reducing the preparation cost and cycle.

CN119530587APending Publication Date: 2025-02-28KONFOONG MATERIALS INTERNATIONAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411742229.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, the density of titanium-aluminum composite materials is low, resulting in poor film formation uniformity, affecting their various properties, and the preparation process is complex and costly, making it difficult to prepare large-sized materials.

Method used

The titanium powder and aluminum powder are mixed evenly by ball milling, and the material is heat isostatically formed using the cover, and the ball milling time, hot isostatic temperature and pressure are controlled to prepare a titanium-aluminum composite material with high density and uniformity.

Benefits of technology

It significantly improves the density of titanium-aluminum composite materials, improves film formation uniformity, reduces preparation costs and cycles, and solves problems such as easy agglomeration of material particles and difficult forming.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530587A_ABST
    Figure CN119530587A_ABST
Patent Text Reader

Abstract

The invention relates to a titanium-aluminum composite material and a preparation method and application thereof, and the preparation method comprises the following steps: ball-milling and mixing titanium powder and aluminum powder, sequentially carrying out die filling, sheath welding and hot isostatic pressing treatment, and then sequentially carrying out sheath removal and machining to obtain the titanium-aluminum composite material, the diameter of the titanium-aluminum composite material ranges from 250 mm to 350 mm, and the thickness of the titanium-aluminum composite material ranges from 450 mm to 550 mm. The titanium powder and the aluminum powder are uniformly mixed through ball-milling mixing, the material is subjected to hot isostatic pressing forming through the sheath, the cost is low, the density improvement effect is remarkable, the large-size titanium-aluminum composite material can be prepared through hot isostatic pressing, batch production of the material is facilitated, the preparation period is greatly shortened, and the production cost is reduced. The problems that titanium-aluminum composite material particles are prone to agglomeration, difficult to form, low in density and uneven in structure are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and relates to a composite material and a preparation method and application thereof, and in particular to a titanium-aluminum composite material and a preparation method and application thereof. Background Art

[0002] At present, titanium-aluminum composite materials are regarded as an important direction for the development of metal composite plates due to their light weight, high strength, high wear resistance and high corrosion resistance, and have shown broad application prospects in the fields of aerospace, petrochemicals, etc. Titanium-aluminum composite materials are used in coating, and TiN, AlN, TiAlN and other coatings can be formed on the surface of the tool under a nitrogen atmosphere. These coatings can increase the surface hardness, corrosion resistance, friction resistance, thermal stability and other parameters, and can also improve the performance and life of the tool, and can also change the surface color of the workpiece.

[0003] In the prior art, the aluminum-titanium composite material prepared by hot pressing has a thickness of several to tens of millimeters, which is relatively small, limiting the application scope of the titanium-aluminum composite material. To prepare an aluminum-titanium composite material with a thickness of several hundred millimeters, the preparation process is complicated, the preparation cost is high, and the prepared aluminum-titanium composite material has a low density, which seriously reduces the uniformity of the film and affects the various properties of the film.

[0004] CN116987921A discloses a TiAl-based composite material with a full lamellar mesh structure and a preparation method thereof, the method comprising: 1. selecting spherical TiAl pre-alloyed powder, metal powder and reinforcement powder; 2. subjecting the spherical TiAl pre-alloyed powder and the metal powder to a primary high-energy ball milling treatment to obtain a TiAl alloy powder with a transition layer on the surface; 3. subjecting the TiAl alloy powder with a transition layer on the surface and the reinforcement powder to a secondary high-energy ball milling treatment to obtain a TiAl alloy powder with the reinforcement uniformly coated on the surface; 4. screening to obtain the powder to be sintered; 5. three-stage temperature sintering. The present invention introduces a transition layer through high-energy ball milling, improves the bonding performance of the reinforcement and the matrix powder, makes the reinforcement powder uniformly coated on the surface of the transition layer, eliminates the ball milling agglomeration phenomenon of the reinforcement, obtains a TiAl-based composite material with a full lamellar mesh structure, and greatly improves the high-temperature strength and microstructural stability of the TiAl-based composite material. The TiAl-based composite material prepared by the invention has a diameter of 50 mm, and a TiAl-based composite material with a larger thickness cannot be prepared.

[0005] CN116275115A discloses an electron beam selective additive manufacturing method for TiAl alloy, which relates to the technical field of electron beam additive manufacturing. The method comprises the following steps: S1. TiAl alloy rods are used to obtain TiAl alloy powder; S2. The TiAl alloy powder is selected to have a suitable particle size distribution; S3. The sieved TiAl alloy powder is mixed evenly; S4. The TiAl alloy powder obtained in step S3 is sent to the electron beam device together with the substrate; S5. The substrate is preheated; S6. Electron beam forming is started, the TiAl alloy powder is spread on the substrate, and powder preheating-solid melting-solid preheating is performed in sequence to complete the single-layer forming; S7. The processing platform is lowered by a layer thickness height, and step S6 is repeated; S8. Step S7 is repeated to obtain the TiAl alloy. The present invention solves the powder blowing problem of electron beam forming by exploring the powder characteristic interval and preheating process. The invention prepares the TiAl alloy by multiple single-layer forming, but its uniformity is greatly reduced.

[0006] Titanium-aluminum composite materials have different properties between titanium powder and aluminum powder. In the prior art, the preparation process is complicated and costly, and the prepared aluminum-titanium composite materials have low density, which seriously affects the large-scale application of the materials. Therefore, how to prepare aluminum-titanium composite materials with high density, good uniformity and low cost has become an urgent problem to be solved. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a titanium-aluminum composite material and a preparation method and application thereof. Titanium powder and aluminum powder are evenly mixed by ball milling, and the material is hot isostatically pressed using a sheath. The cost is low and the density improvement effect is significant. Moreover, a large-sized titanium-aluminum composite material can be prepared by hot isostatic pressing, which is convenient for mass production of materials and greatly shortens the preparation cycle, solving the problems of easy agglomeration of titanium-aluminum composite material particles, difficulty in molding, low density, and uneven organization.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a titanium-aluminum composite material, the preparation method comprising the following steps: ball milling mixed titanium powder and aluminum powder, sequentially performing molding, sheath welding and hot isostatic pressing, and then sequentially performing sheath removal and machining to obtain the titanium-aluminum composite material; the titanium-aluminum composite material has a diameter of 250mm-350mm and a thickness of 450mm-550mm.

[0010] Specifically, the diameter can be 250mm, 270mm, 290mm, 300mm, 330mm or 350mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the thickness can be 450mm, 470mm, 490mm, 500mm, 530mm or 550mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0011] The present invention mixes titanium powder and aluminum powder evenly by ball milling, and uses a sheath to perform hot isostatic pressing on the material, which has low cost and significant density improvement effect. Moreover, a large-sized titanium-aluminum composite material can be prepared by hot isostatic pressing, which is convenient for mass production of materials, greatly shortens the preparation cycle, and solves the problems of easy agglomeration of titanium-aluminum composite material particles, difficulty in forming, low density, and uneven organization.

[0012] Preferably, the particle size D50 of the titanium powder is 5 μm-50 μm, for example, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm or 50 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] Preferably, the particle size D50 of the aluminum powder is 5 μm-65 μm, for example, 5 μm, 10 μm, 30 μm, 50 μm, 60 μm or 65 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the mass ratio of the titanium powder to the aluminum powder is (1-5):1, for example, 1:1, 2:1, 3:1, 4:1 or 5:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the ball milling mixing time is 12h-48h, for example, 12h, 24h, 36h, 40h or 48h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0016] The present invention can avoid the agglomeration of materials due to excessive ball milling and ensure the uniformity and dispersibility of materials by regulating the ball milling time. On the other hand, it can narrow the distribution range of powder particle size to a certain extent and further improve the uniformity of material mixing. Within the preferred ball milling time, a titanium-aluminum composite material with large size, high density and uniform structure is prepared.

[0017] Preferably, the ball milling mixing method comprises planetary ball milling.

[0018] Preferably, the spindle speed of the ball milling mixing is 3r / min-10r / min, for example, it can be 3r / min, 5r / min, 7r / min, 9r / min or 10r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the planetary disk rotation speed of the ball milling mixing is 40r / min-120r / min, for example, it can be 40r / min, 60r / min, 80r / min, 100r / min or 120r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the ball-to-material ratio of the ball milling mixture is (2-8):1, for example, it can be 2:1, 4:1, 5:1, 6:1 or 8:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the filling density of the mold is 51%-65%, for example, it can be 51%, 55%, 58%, 60% or 65%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the size of the mold is diameter (250mm-350mm)×thickness (450mm-550mm), for example, it can be diameter 250mm×thickness 450mm, diameter 300mm×thickness 500mm, diameter 350mm×thickness 500mm or diameter 350mm×thickness 550mm.

[0023] Preferably, the holding temperature of the hot isostatic pressing is 300°C-500°C, for example, 300°C, 350°C, 400°C, 450°C or 500°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] The present invention further regulates the holding temperature of hot isostatic pressing, which is beneficial to uniform molding of the material, thereby obtaining a titanium-aluminum composite material with uniform structure, and can avoid the influence of alloying reaction on the density of the material. Within the preferred hot isostatic pressing temperature range, the titanium-aluminum composite material prepared by the present invention has high density and uniform structure.

[0025] Preferably, the pressure of the hot isostatic pressing is 100 MPa-120 MPa, for example, 100 MPa, 105 MPa, 110 MPa, 115 MPa or 120 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] The present invention can improve the density of the material, further shorten the time required for material molding, and reduce the temperature required for material molding by further regulating the pressure of hot isostatic pressing. On the other hand, it can reduce the use requirements of the sheath material, increase the service life of the equipment, reduce the production cost, and facilitate the mass production of the material. Within the preferred hot isostatic pressing pressure range, the prepared titanium-aluminum composite material has high density and uniform structure, and the preparation process is low in cost and high in efficiency.

[0027] Preferably, the holding time of the hot isostatic pressing is 2h-7h, for example, 2h, 3h, 4h, 5h, 6h or 7h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] The present invention can improve the density of the material by regulating the holding time of hot isostatic pressing, and can reduce the production cost and facilitate mass production of the material. Within the preferred holding time of hot isostatic pressing, the prepared titanium-aluminum composite material has high density and uniform structure, and the preparation process has low cost and high efficiency.

[0029] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0030] (1) Mix titanium powder and aluminum powder in a ball mill for 12 h to 48 h to obtain a mixed powder.

[0031] (2) The mixed powder is sequentially subjected to mold filling, sheath welding and degassing treatment to obtain a sheath structure.

[0032] (3) The package structure is subjected to hot isostatic pressing at 300°C-500°C and 100MPa-120MPa, and the pressure is maintained for 2h-7h.

[0033] (4) removing the sheath and performing machining to obtain the titanium-aluminum composite material.

[0034] In a second aspect, the present invention provides an aluminum-titanium composite material, which is prepared by the preparation method described in the first aspect.

[0035] Preferably, the density of the aluminum-titanium composite material is 90%-99%, for example, it can be 90%, 92%, 95%, 97%, 98% or 99%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the diameter of the aluminum-titanium composite material is 250 mm-350 mm, for example, it can be 250 mm, 270 mm, 290 mm, 300 mm, 330 mm or 350 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the thickness of the aluminum-titanium composite material is 450 mm-550 mm, for example, 450 mm, 470 mm, 490 mm, 500 mm, 530 mm or 550 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In a third aspect, the present invention provides an application of the aluminum-titanium composite material as described in the second aspect, wherein the aluminum-titanium composite material is applied to a vapor deposition substrate.

[0039] Compared with the prior art, the present invention has at least the following beneficial effects:

[0040] The present invention mixes titanium powder and aluminum powder evenly by ball milling, and uses a sheath to perform hot isostatic pressing on the material, which has low cost and significant density improvement effect. Moreover, a large-sized titanium-aluminum composite material can be prepared by hot isostatic pressing, which is convenient for mass production of materials, greatly shortens the preparation cycle, and solves the problems of easy agglomeration of titanium-aluminum composite material particles, difficulty in forming, low density, and uneven organization. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the organizational morphology of the titanium-aluminum composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0043] Example 1

[0044] This embodiment provides a method for preparing a titanium-aluminum composite material, the preparation method comprising the following steps:

[0045] (1) 5 parts by mass of titanium powder and 5 parts by mass of aluminum powder were ball-milled and mixed in a ball mill for 24 hours, wherein the D50 of the titanium powder was 50 μm, the D50 of the aluminum powder was 65 μm, the ball-to-material ratio was 4:1, the spindle speed was 5 r / min, and the planetary disk speed was 50 r / min, to obtain a mixed powder;

[0046] (2) The mixed powder is subjected to mold filling, sheath welding and degassing treatment in sequence, wherein the mold size of the mold filling is 300 mm in diameter × 500 mm in thickness, and the filling density of the mold filling is 60%, to obtain a sheath structure;

[0047] (3) The package structure is subjected to hot isostatic pressing at 450°C and 105 MPa, and the pressure is maintained for 5 hours;

[0048] (4) removing the sheath and performing machining to obtain the titanium-aluminum composite material.

[0049] Figure 1 This is the organizational morphology of the titanium-aluminum composite material prepared in this example. It can be seen from the figure that the prepared titanium-aluminum composite material has uniform organization and high density.

[0050] Example 2

[0051] This embodiment provides a method for preparing a titanium-aluminum composite material, the preparation method comprising the following steps:

[0052] (1) 5 parts by mass of titanium powder and 1 part by mass of aluminum powder were ball-milled and mixed in a ball mill for 12 hours, wherein the D50 of the titanium powder was 5 μm, the D50 of the aluminum powder was 5 μm, the ball-to-material ratio was 2:1, the spindle speed was 3 r / min, and the planetary disk speed was 120 r / min, to obtain a mixed powder;

[0053] (2) The mixed powder is subjected to mold filling, sheath welding and degassing treatment in sequence, wherein the mold size of the mold filling is 250 mm in diameter × 450 mm in thickness, and the filling density of the mold filling is 51%, to obtain a sheath structure;

[0054] (3) The package structure is subjected to hot isostatic pressing at 300°C and 120 MPa for 7 hours;

[0055] (4) removing the sheath and performing machining to obtain the titanium-aluminum composite material.

[0056] Example 3

[0057] This embodiment provides a method for preparing a titanium-aluminum composite material, the preparation method comprising the following steps:

[0058] (1) 4 parts by mass of titanium powder and 4.5 parts by mass of aluminum powder were ball-milled and mixed in a ball mill for 48 hours, wherein the D50 of the titanium powder was 20 μm, the D50 of the aluminum powder was 30 μm, the ball-to-material ratio was 8:1, the spindle speed was 10 r / min, and the planetary disk speed was 40 r / min, to obtain a mixed powder;

[0059] (2) The mixed powder is subjected to mold filling, sheath welding and degassing treatment in sequence, wherein the mold size of the mold filling is 350 mm in diameter × 550 mm in thickness, and the filling density of the mold filling is 65%, to obtain a sheath structure;

[0060] (3) The package structure is subjected to hot isostatic pressing at 500°C and 100 MPa, and the pressure is maintained for 2 hours;

[0061] (4) removing the sheath and performing machining to obtain the titanium-aluminum composite material.

[0062] Example 4

[0063] The difference between this embodiment and embodiment 1 is that, except for the time of ball milling mixing in step (1) being 10 hours, the rest is the same as embodiment 1.

[0064] Example 5

[0065] The difference between this embodiment and embodiment 1 is that, except for the time of ball milling mixing in step (1) being 50 hours, the rest is the same as embodiment 1.

[0066] Example 6

[0067] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of hot isostatic pressing in step (3) is 250° C., the rest is the same as embodiment 1.

[0068] Example 7

[0069] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of hot isostatic pressing in step (3) is 550° C., the rest is the same as embodiment 1.

[0070] Example 8

[0071] The only difference between this embodiment and embodiment 1 is that, except that the pressure of hot isostatic pressing in step (3) is 95 MPa, the rest is the same as embodiment 1.

[0072] Example 9

[0073] The only difference between this embodiment and embodiment 1 is that, except that the pressure of hot isostatic pressing in step (3) is 125 MPa, the rest is the same as embodiment 1.

[0074] Example 10

[0075] The only difference between this embodiment and embodiment 1 is that, except for the holding time of hot isostatic pressing in step (3) being 1.5 h, the rest is the same as embodiment 1.

[0076] Embodiment 11

[0077] The only difference between this embodiment and embodiment 1 is that, except for the holding time of hot isostatic pressing in step (3) being 7.5 h, the rest is the same as embodiment 1.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 1 is that, except for the mixing method in step (1), the rest are the same as Example 1.

[0080] Comparative Example 2

[0081] The difference between this comparative example and Example 1 is that, except that hot isostatic pressing is not performed in step (3), the rest is the same as Example 1.

[0082] Test Method

[0083] The titanium-aluminum composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 2 were subjected to a density test. The test method was as follows: the actual density of the titanium-aluminum composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 2 was measured by a drainage method, and the density was calculated by comparing it with the theoretical density. The test results were recorded in Table 1.

[0084] Table 1

[0085]

[0086]

[0087] The test results show that:

[0088] (1) It can be seen from Examples 1 to 11 and Comparative Examples 1 to 2 that the present invention mixes titanium powder and aluminum powder uniformly by ball milling, and uses a sheath to perform hot isostatic pressing on the material, which is low in cost and has a significant effect on improving density. In addition, a large-sized titanium-aluminum composite material can be prepared by hot isostatic pressing, which is convenient for mass production of materials, greatly shortens the preparation cycle, and solves the problems of easy agglomeration of titanium-aluminum composite material particles, difficulty in forming, low density, and uneven organization.

[0089] (2) It can be seen from Example 1 and Example 4-Example 5 that the density of the titanium-aluminum composite material prepared by the present invention is further improved by further adjusting the ball milling mixing time.

[0090] (3) It can be seen from Example 1 and Example 6-Example 7 that the density of the titanium-aluminum composite material prepared by the present invention is further improved by further adjusting the holding temperature of the hot isostatic pressing.

[0091] (4) It can be seen from Example 1 and Example 8-Example 9 that the density of the titanium-aluminum composite material prepared by further adjusting the hot isostatic pressing pressure in the present invention is further improved.

[0092] (5) It can be seen from Example 1 and Example 10-Example 11 that the density of the titanium-aluminum composite material prepared by the present invention is further improved by further adjusting the holding time of hot isostatic pressing.

[0093] In summary, the present invention mixes titanium powder and aluminum powder evenly through ball milling, and uses a sheath to perform hot isostatic pressing on the material, which is low-cost and has a significant effect on improving density. In addition, large-sized titanium-aluminum composite materials can be prepared by hot isostatic pressing, which is convenient for mass production of materials, greatly shortens the preparation cycle, and solves the problems of easy agglomeration of titanium-aluminum composite material particles, difficulty in forming, low density, and uneven organization.

[0094] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a titanium-aluminum composite material, characterized in that: The preparation method comprises the following steps: ball milling titanium powder and aluminum powder, sequentially performing mold filling, jacket welding and hot isostatic pressing, and then sequentially performing jacket removal and machining to obtain the titanium-aluminum composite material; The titanium-aluminum composite material has a diameter of 250 mm to 350 mm and a thickness of 450 mm to 550 mm.

2. The preparation method according to claim 1, characterized in that: The particle size D50 of the titanium powder is 5 μm-50 μm; Preferably, the particle size D50 of the aluminum powder is 5 μm-65 μm; Preferably, the mass ratio of the titanium powder to the aluminum powder is (1-5):

1.

3. The preparation method according to claim 1 or 2, characterized in that: The ball milling mixing time is 12h-48h.

4. The preparation method according to claim 3, characterized in that: The ball milling mixing method includes planetary ball milling; Preferably, the spindle speed of the ball milling mixing is 3r / min-10r / min; Preferably, the planetary disc speed of the ball milling mixing is 40r / min-120r / min; Preferably, the ball-to-material ratio of the ball milling mixture is (2-8):

1.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The packing density of the mold is 51%-65%; Preferably, the size of the mold for molding is diameter (250mm-350mm)×thickness (450mm-550mm).

6. The preparation method according to any one of claims 1 to 5, characterized in that: The holding temperature of the hot isostatic pressing is 300° C.-500° C.; Preferably, the hot isostatic pressing pressure is 100MPa-120MPa; Preferably, the holding time of the hot isostatic pressing is 2h-7h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing titanium powder and aluminum powder in a ball mill for 12 h to 48 h to obtain a mixed powder; (2) subjecting the mixed powder to mold filling, sheath welding and degassing treatment in sequence to obtain a sheath structure; (3) subjecting the package structure to hot isostatic pressing at 300°C-500°C and 100MPa-120MPa, and maintaining the pressure for 2h-7h; (4) removing the sheath and performing machining to obtain the titanium-aluminum composite material.

8. An aluminum-titanium composite material, characterized in that: The aluminum-titanium composite material is prepared by the preparation method described in any one of claims 1 to 7.

9. The aluminum-titanium composite material according to claim 8, characterized in that: The density of the aluminum-titanium composite material is 90%-99%.

10. An application of the aluminum-titanium composite material as claimed in claim 8 or 9, characterized in that: The aluminum-titanium composite material is applied to vapor deposition sputtering.

Citation Information

Cited By

  • Light composite metal material and preparation method thereof

    CN120790902A